UTILIZATION OF CLIMATE-SMART POSTHARVEST LOSS REDUCTION STRATEGIES BY SMALLHOLDER CASSAVA FARMERS IN SOUTHEAST, NIGERIA - Agou, G. D.; Nwaogu, D. C.; Ololo, K. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed utilization of climate-smart post-harvest loss reduction strategies by smallholder cassava farmers in Southeast, Nigeria. Multi-stage sampling procedure was used in selecting 240 respondents. Data were collected through the administration questionnaire and analyzed using percentage, mean score and tobit regression. The study revealed that majority (71.3%) of the respondents were males, with an average age, farming experience and household size of 48.4 years, 18.5 years and 6 persons, respectively. The results also showed that the use of ground storage (66.3%), hermatic bags (65.4%) and evaporative cooling structures (61.3%) were the most utilized climate-smart post-harvest loss reduction strategies utilized by the smallholder cassava farmers in the study area. The results further revealed that difficulties in getting improved cassava varieties (x ̅=3.41), lack of formal education (x ̅=3.41) and high cost of labour (x ̅=3.38) were some of the challenges faced in the use of post-harvest loss reduction strategies. The study concluded age (p<0.05), farming experience (p<0.05), household size (p<0.05), farm size (p<0.05), access to credit (p>0.05) and cooperative membership (p<0.05) were the factors affecting the utilization of climate-smart postharvest loss reduction strategies among smallholder cassava farmers in the study area. The study recommends that relevant government agents such extension personnel should train cassava farmers on modern climate-smart post-harvest loss reduction strategies to ensure increased cassava production and profitability.